An Analysis Of English - Indonesian Text Translation Of Associated Press News Agency In Olahraga Column In Solopos - Cahyono, Indra Dwi (2005)
The research is a descriptive study which focuses on the analysis of the translation types used and the accuracy of the translation based on the structure and the message. The data of this research consists of 100 sentences in the text of Olahraga column published in March 2004. Based on the types of translation used in Olahraga Column, there are two types, namely; literal translation and free translation. Literal translation occurs in 76 data or 76% out of the whole data analyzed. Free translation occurs in 24 data or 24% out of the total data analyzed. Based on the accuracy of the translation in the terms of the structure and the message, the data are classified into the sentences that are translated accurately in terms of structure and the message 61 data or 61 % , the sentences that are translated accurately in terms of the message only occur in 16 data or 16%. The sentences that are translated correctly in terms of the structure only are included in 15 or 15%, and the sentences that are translated inaccurately both in terms of structure and the message occur in 8 or 8% out of the whole data analyzed. These phenomena indicate that the English-Indonesian translation of the text published in Olahraga column in Solopos is good considering that more than 50% out of the data analyzed are accurately translated. The inaccurate occurring in the translation include the use of inappropriate TL equivalences, the use of informal TL words and expressions, the omission of important units of sentences or addition of unnecessary units in sentences, and the lack of punctuation marks in the writing of sentences.